The Influence of Brand Ambassador, Brand Awareness, Brand Image and Prices on Purchase Decisions on Online Marketplace - Carla Clarissa; Innocentius Bernarto (Universitas Trisakti, 2022)
Currently the marketplace is competing for a strong positioning in the minds of its customers. Companies show business by presenting brand ambassadors, brand awareness, brand image, and prices so that consumers have the intention to buy products or services. Thus, the brand will be embedded in people's memories and expectations of consumers' interest in buying products or services. The research was in a quantitative way and has the type of cause-and-effect association research. This research uses incidental non-probability sampling technique. The data analysis technique used is SEM-PLS. Based on the results of the study, brand ambassador has a significant effect on purchasing decisions. The result showed that the higher the consumer's positive perception of the brand ambassador, the higher the purchase decision. Brand awareness has a significant effect on purchasing decisions. The higher the brand awareness of consumers, the higher the purchase decision. Brand image also has a significant effect on purchasing decisions. The higher the brand image of a product, the higher the purchase decision. Price has a significant effect on purchasing decisions. The more appropriate the price with a product, the higher the purchase decision.